Wireless data acquisition system - Areza, Benjamin Randy S. (Animo Repository, 1993)
This thesis discusses the design and implementation of a wireless (radio frequency) data acquisition system to automatically monitor physical quantities in an industrial or manufacturing environment. For purposes of demonstration, only temperature and pressure quantities are studied.A Z80 module is developed to handle the task of data collection from sensors and conversion of the digital data into analog voice-grade signals. Output signals are then fed to the transceiver for radio transmission. Errors due to interference, underrun, and framing are overcome by software error detection.On the other side, a Central Monitoring Terminal module is built to capture the data transmitted by the Z80 module. The program collects the data and decode it into its true value using a pre-determined look-up table.